(3ehGLgI GdEQgGH Hjf GdSjGSI GdJTQjYjI hGdTQYjI GdLfGFjI (B/s - (3CHh Gddjd eUWaj CHh Gddjd SQMGfs; (3CMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3JJeMhQ GdQSGdI Mhd ehGLgI GdEQgGH Hjf GdSjGSI GdJTQjYjI hGdTQYjI GdLfGFjI OQGSI ebGQfI, HGYJHGQ Cf XGgQI GdEQgGH GoHJdjJ HgG cd GdeLJeYGJ, heY GdJWhQ GdPj MOK aj GdYGde HGJ GdEQgGH LQjeI JJHY aj WQbgG cGaI eYGde GdJcfhdhLjG GdMOjKI(B. (3MjK YGfJ efg GdeLJeYGJ bOjkeG hMOjkKG, Ydi GNJdGa KbGaJgG hbjegG, HeNJda UhQg hhSGFdg(B. (3aLGAJ GdQSGdI eTJedI Ydi HGHjf; jSHbgeG aUd JegjOj, JfGhdfG aj gPG GdaUd GdJegjOj HjGf eGgjI GdLQjeI GdEQgGHjI hWHjYJgG GdbGfhfjI(B. (3CeG GdHGH GdChd ajgG aNUUfGg dOQGSI GdehGLgI GdLfGFjI GdehVhYjI ddLQGFe GdEQgGHjI, hCTJed Ydi aUdjf; JfGhdfG aj GdaUd GdChd(B: (3GdCMcGe GdYGeI dehGLgI GdLQGFe GdEQgGHjI(B. (3dfdMb Hg JCUjd GdLQGFe GdEQgGHjI, aj GdaUd GdKGfj(B: (3Ke JfGhdfG aj GdHGH GdKGfj ef gPg GdQSGdI GdehGLgI GdLfGFjI GdELQGFjI ddLQGFe GdEQgGHjI(B: (3hbO befG HJbSe gPG GdHGH Edi aUdjf; NUUfG GdaUd GdChd dOQGSI CMcGe GdehGLgI GdLfGFjI GdELQGFjI, CeG GdaUd GdKGfj aNUUfGg dOQGSI BdjGJ GdJYGhf GdOhdj GdLfGFj aj eLGd ecGaMI GdEQgGH s
The thesis centers on confronting terrorism between legislative policy and criminal legitimacy, a comparative study, given that the phenomenon of terrorism afflicts all societies, and with the development that occurred in the world, terrorism has become a crime that follows in its ways all the features of modern technology. Societies have suffered from it, past and present, with different cultures and values, in its various forms and means. The letter came to include two chapters; They are preceded by an introductory chapter. In this introductory chapter, we dealt with the definition of the terrorist crime and its legal nature. As for the first chapter, we devoted it to the study of the objective criminal confrontation of terrorist crimes, and it included two chapters; In the first chapter, we discussed the general provisions for countering terrorist crimes. Let us add to it the rooting of terrorist crimes, in the second chapter: Then, in the second chapter of this thesis, we dealt with the criminal and procedural confrontation of terrorist crimes: We have divided this chapter into two chapters; We devoted the first chapter to studying the provisions of procedural criminal confrontation, while the second chapter was devoted to studying the mechanisms of international criminal cooperation in the field of combating terrorism.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2023s
(3HHdjhLQGajG(B: (3UaMGJ (B331-361.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdLQjeI GdEQgGHjIs; (3GdEQgGHs; (3bGfhf (B94 (3dSfI (B2015s; (3GdLeGYGJ GdGQgGHjIs; (3LQjeI GdSYjs; (3LQjeI GdJNGHQ eY OhdI GLfHjIs; (3GdJYGhf GdOhdj GdLfGFjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs